a^4-b^2.(2a-b)^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
$x^3-6x^2+12x-8=0$
$\Leftrightarrow (x-2)^3=0$
$\Leftrightarrow x-2=0$
$\Leftrightarrow x=2$
\(x^3-6x^2+12x-8=0\)
`<=>x^3-3.x^3.2+3.x.2^2-2^3=0`
`<=>(x-2)^3=0`
`<=>x-2=0`
`<=>x=2`
\(x^3+9x^2+27x+27=0\)
\(\Leftrightarrow x^3+3.x^2.3+3.x.3^2+3^3=0\)
\(\Leftrightarrow\left(x+3\right)^3=0\)
`<=>x+3=0`
`<=>x=-3`
\(x^3+9x^2+27x+27=0\)
\(\Leftrightarrow x^3+3.3.x^2+3.9x+3^3=0\)
\(\Leftrightarrow\left(x+3\right)^3=0\)
\(\Rightarrow x+3=0\Rightarrow x=-3\)
1 Tom didn't fix the refrigerator last monday
2 did her husband put a bunch of flowers on her desk?
3 she wasn't helping her dad at 11 am yesterday
4 were most of them safe after the accident?
5 he wasn't making any hot chocolate at 1:30 this morning
6 was I looking for my watch when the phone rang?
7 were you so scared when we heard a strange sound?
8 Anna didn't eat a lot of pizza at the party last night
9 did the doctor wash her hands after touching the patients?
`x-4` mũ `2=36`
TH1
`x-4=6`
`x=10`
TH2
`x-4=-6`
`x=-2`
Vậy `x=10` hoặc `x=-2`
(x - 4)2 - 36 = 0
(x - 4)2 = 0 + 36
(x - 4)2 = 36
(x - 4)2 = 62 = (-6)2
TH1 : (x - 4)2 = 62
x - 4 = 6
x = 6 + 4
x = 10
TH2 : (x - 4)2 = (-6)2
x - 4 = -6
x = -6 + 4
x = -2
vậy x ϵ {-2;10}
Đề sai à bn
đề tui đúng mà